Fulfillment of the Right of Access to Justice Through the Application of Restorative Justice Principles for Women Facing the Law - Undang Abdul Mutolib; Nanun Abdillah; Asep Irfan; Imam Sucipto; Mujio Nurkholis (Zona Law And Public Administration Indonesia, 2023)
The right to obtain justice is a human right that must be respected, protected, and fulfilled by the state. "However, currently the fulfillment of the right to obtain justice is still far from expectations. The research method used is normative juridical or literature research related to normative legal substance, to find truth based on scientific logic viewed from the normative side by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study show that in prosecuting women facing the law, judges have considerations based on the facts at trial, exploring the values that live in society, international conventions and agreements related to gender equality that have been ratified. The state makes regulations for judges as a guideline in prosecuting women against the law, to ensure gender equality, equal protection and non-discrimination